Current Barriers to Clinical Liver Xenotransplantation - Cross-Najafi, Arthur A.; Lopez, Kevin; Isidan, Abdulkadir; Park, Yujin; Zhang, Wenjun; Li, Ping; Yilmaz, Sezai; Akbulut, Sami; Ekser, Burcin (Frontiers in Immunology, 2022)
Preclinical trials of pig-to-nonhuman primate liver xenotransplantation have recently achieved longer survival times. However, life-threatening thrombocytopenia and coagulation dysregulation continue to limit preclinical liver xenograft survival times to less than one month despite various genetic modifications in pigs and intensive pharmacological support. Transfusion of human coagulation factors and complex immunosuppressive regimens have resulted in substantial improvements in recipient survival. The fundamental biological mechanisms of thrombocytopenia and coagulation dysregulation remain incompletely understood. Current studies demonstrate that porcine von Willebrand Factor binds more tightly to human platelet GPIb receptors due to increased O-linked glycosylation, resulting in increased human platelet activation. Porcine liver sinusoidal endothelial cells and Kupffer cells phagocytose human platelets in an asialoglycoprotein receptor 1-dependent and CD40/CD154-dependent manner, respectively. Porcine Kupffer cells phagocytose human platelets via a species-incompatible SIRPα/CD47 axis. Key drivers of coagulation dysregulation include constitutive activation of the extrinsic clotting cascade due to failure of porcine tissue factor pathway inhibitor to repress recipient tissue factor. Additionally, porcine thrombomodulin fails to activate human protein C when bound by human thrombin, leading to a hypercoagulable state. Combined genetic modification of these key genes may mitigate liver xenotransplantation-induced thrombocytopenia and coagulation dysregulation, leading to greater recipient survival in pig-to-nonhuman primate liver xenotransplantation and, potentially, the first pig-to-human clinical trial.